2006
DOI: 10.1007/s10545-006-0208-0
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric dimethylarginine in homocystinuria due to cystathionine β‐synthase deficiency: Relevance of renal function

Abstract: ADMA levels were significantly increased only in the CBS-deficient patients with elevated cystatin C levels, and not in those with normal renal function. The reported relationship between hyperhomocysteinaemia and ADMA may not be direct, but could be secondary to reduced renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 43 publications
2
10
0
1
Order By: Relevance
“…The ADMA levels in our study population are in accordance with those of the others [20,[23][24][25]. In the dialysis patients, dimethylarginines were further increased: the SDMA concentration was about 3.5-fold higher in the early stage patients, whereas more than sevenfold higher both in PD and HD patients when compared to healthy controls.…”
Section: Discussionsupporting
confidence: 91%
“…The ADMA levels in our study population are in accordance with those of the others [20,[23][24][25]. In the dialysis patients, dimethylarginines were further increased: the SDMA concentration was about 3.5-fold higher in the early stage patients, whereas more than sevenfold higher both in PD and HD patients when compared to healthy controls.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the association between plasma ADMA and Hcy levels is observed in many animal and clinical studies. High Hcy concentrations might elevate ADMA by inhibiting dimethylarginine dimethylaminohydrolase (DDAH), the ADMA metabolizing enzyme, activity (Dayal & Lentz, 2005;Stühlinger et al, 2001;Wilcken et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The endothelium is the primary target of destruction arising from chemical and mechanical factors. Endothelial dysfunction, either as a cause or a consequence, is now known to be associated with a spectrum of cardiovascular diseases (Bestermann, 2011;Dayal & Lentz, 2005;Wilcken et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This could underlie an impaired endothelium-dependent NO-mediated vasodilatation induced by homocysteine in the pig aorta (167). However, more recent data has shown that ADMA accumulates in patients with hyperhomocysteinemia only with the development of renal dysfunction (215).…”
Section: Expression and Function Of Ddah In Diseasementioning
confidence: 99%